INSTITUTIONAL ENVIRONMENT INFLUENCE OF MICRO AND MACRO FACTORS ON THE ACTIVITY OF GAS DISTRIBUTION ENTERPRISES OF THE REGION (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article is devoted to the topical issues of the institutional capacity of the gas distribution companies, which covers the range of institutional units that will determine the vector and further activities of gas distribution companies. Among the factors of influence on the institutional environment, I was grouped by factors of microeconomic and macroeconomic character. In addition, the article reflects the characteristic features of the institutional environment by reducing the image of the international arena, the ineffectual policy, imbalance the legal basis that will reduce the monopoly pressure due to the restructuring of the NAK "Naftogaz" and the dissemination of the competitive environment and the formation of an independent regulator. The main institutions and institutions of direct and indirect influence are characterized. It is proved that in providing necessary and favorable institutional environment belongs to the bodies of general and special competence. The goal of the article is clarification of theoretical and practical approaches to institutionalizing the objects of the gas transportation sector. To achieve the goal, a number of tasks were defined: to find out the concept of "invariant environment" of gas distribution companies; Isolate factors of microeconomic and macro-economic nature of influence on the intitle environment; Predict the rectrospecative scenario of future activity of gas distribution companies in the context of gas market liberalization. Having determined the role and place of micro and macroeconomic factors to ensure the institutional environment of the operation of Gas market, it is worth highlighting a number of effects of socio-economic orientation on the environment: rational use of material and personal resources; Purpose of investment for modernization purposes; Control exchange of quality and consumption of natural gas; Operating modern business methods and tools of operational management; Compliance with environmental safety standards; Optimization of tariffs between the gas supply and the final price of gas; Harmonization of relationships between partners and consumers; development of infrastructure; Legal basis for the protection of interests of gas transportation companies; Formation of a single chain of goals: "State-gas transport sphere-consumer"; minimization of transaction expenses; Expanding the boundaries of experience in acquiring professional skills.
Keywords: institutionalization, institutional environment, gas transportation system, gas distribution companies, microeconomic factor, macroeconomic factor, mesoeconomics.